The Fluoride Concentration of Bottled Drinking Water in Al-Basra City, Iraq - Bahaa A Jeri (College of Dentistry/ University of Baghdad, 2016)
Background: This study aimed to determine the amount of fluoride in commercially available bottled drinking water in Al-Basra city, Iraq Materials and Methods: Eleven brands of bottled drinking water were obtained from supermarkets in Al-Basra city, Iraq. Five samples of 10 ml. were taking from each one of brands and the fluoride was determined by using fluoride ion selective electrode. Results: The highest fluoride concentration was present in BADIOT brand (1.174 mg/L) while the lowest was in Barakat brand (0.038 mg/L). One way ANOVA test showed a highley significant difference among different commercially branded types. Coclusions: Bottled water available in Al-Basra city contains less concentration of fluoride ion than normal values because there is no adding of fluoride to the water. Key words: Bottled water, fluoride, Al-Basra, Iraq.